Effect of disaccharides of different composition and linkage on corn and waxy corn starch retrogradation. (December 2016) - Wang, Lili; Xu, Jin; Fan, Xuerong; Wang, Qiang; Wang, Ping; Zhang, Ying; Cui, Li; Yuan, Jiugang; Yu, Yuanyuan
Abstract: The effect of disaccharides of different monosaccharide compositions and linkages on corn and waxy corn starch long-term retrogradation was investigated using differential scanning calorimetry (DSC), wide X-ray diffraction (WXRD), and molecular dynamic (MD) simulation. The disaccharides consisted of sucrose (glucose-fructose, α-1, 2 glycosidic bond), lactose (glucose-galactose, β-1, 4 glycosidic bond), and maltose (glucose-glucose, α-1, 4 glycosidic bond). DSC data showed that ΔH (melting enthalpy of retrograded starch) was reduced with the addition of sugars (maltose > lactose > sucrose > glucose > galactose > fructose). The WXRD results revealed that the disaccharides inhibited starch retrogradation. In addition, MD simulation, which was adapted to predict the interaction of disaccharides and starch, confirmed that the disaccharides reduced starch retrogradation. Graphical abstract: Schematic of the disaccharides with different composition and linkage on starch retrogradation. Highlights: Disaccharides significantly affect long-term starch retrogradation. The extent of starch retrogradation is dependent on disaccharide composition. Maltose has greater anti-aging effects than lactose or sucrose.